Interactions Between Neurokinin B and Kisspeptin in Mediating Estrogen Feedback in Healthy Women - Skorupskaite, Karolina (J Clin Endocrinol Metab, 2016)
CONTEXT: Kisspeptin and neurokinin B (NKB) are obligate for normal gonadotropin secretion, but their hierarchy is unexplored in normal women. OBJECTIVE: To investigate the interaction between kisspeptin and NKB on estrogen-regulated LH secretion. DESIGN: Women were treated with neurokinin-3 receptor (NK3R) antagonist followed by transdermal estradiol to induce LH secretion 48 hours later, with kisspeptin-10 or vehicle infusion during estrogen administration in a 2-way crossover study. SETTING: Clinical research facility. PATIENTS OR OTHER PARTICIPANTS: Healthy females with regular menses. INTERVENTION(S): NK3R antagonist AZD4901 40 mg twice daily orally was taken from cycle day 4–6 for 6 days (n = 10, with 10 no treatment controls). Transdermal estradiol patches (200 μg/d) were applied after 5 days of NK3R antagonist treatment. At 24-hour estradiol treatment, women were randomized to 7-hour kisspeptin-10 (4 μg/kg/h) or vehicle iv infusion, with the alternate infusion in a subsequent cycle. MAIN OUTCOME MEASURE(S): Plasma gonadotropin and estradiol secretion. RESULTS: After an initial suppression, LH secretion was increased 48 hours after estradiol treatment. Kisspeptin-10 increased LH secretion during the inhibitory phase, and LH remained elevated beyond the discontinuation of kisspeptin-10 infusion. NK3R antagonist decreased LH pulse frequency (0.5 ± 0.2 vs 0.7 ± 0.2 pulses/h, P < .05) and stimulated FSH response to kisspeptin-10 infusion (10.7 ± 11.0 vs 5.0 ± 3.6 IU/L, P < .05) with a nonsignificant rise in LH. The duration of LH response was blunted, with LH being lower at 48 hours (7.5 ± 4.8 vs 15.0 ± 11.4 IU/L, P < .05). CONCLUSIONS: These data demonstrate that NKB signaling regulates GnRH/LH secretion in normal women, and is predominantly proximal to kisspeptin in mediating estrogenic positive and negative feedback on LH secretion.